Transcriptome analysis unravels key pathways and hub genes related to immature fruit abscission in Camellia oleifera - Ma, Xiaoling; Chen, Shiwen; Li, Jinwen; Ouyang, Xiang (Frontiers in Plant Science, 2024)
Immature fruit abscission of Camellia oleifera (C. oleifera) is a common problem limiting yield increases. However, the regulatory mechanisms underlying immature fruit abscission in C. oleifera are unclear. In this study, we systematically investigated changes in the morphological, physiological, and gene expression of fruit abscission zones (FAZs) of soon-to-abscise fruits (M2). We found that fruit abscission before ripening mainly occurs during the August abscission stage of ‘Huashuo’. At the beginning of this stage, the FAZs of M2 have a marked dent, and the separation layer structures are preliminarily formed. Phytohormone analysis showed that the contents of indole-3-acetic acid (IAA) and jasmonic acid (JA) in the FAZs of M2 were significantly decreased compared with the non-abscised fruits, while the content of trans-zeatin (TZR) was increased. Transcriptome analysis identified differentially expressed genes (DEGs) mainly involved in phytohormone metabolism, including ethylene, auxin, JA, and the cis-zeatin signal transduction pathway. There were also many DEGs involved in cell wall catabolism. Weighted gene co-expression network analysis (WGCNA) further suggested that the transcription factors NAC100 and ERF114 participate in the immature fruit abscission of C. oleifera. This study provides insights into the fruit abscission mechanism of C. oleifera.